The effects of moral/social identity threats and affirmations on psychological defensiveness following wrongdoing. (7th April 2020) - Wenzel, Michael; Woodyatt, Lydia; McLean, Ben
Abstract : Defensive responses to transgressions can have a negative impact on decision‐making within government and organizations, on relationships, and even an individual's well‐being. Transgressors who are defensive are less likely to acknowledge or appreciate the extent of harm caused, and their responsibility in having contributed to it or in helping to repair it. It is therefore important to understand what situational factors increase or reduce defensiveness and, thus, offer solutions for those trying to foster responsibility‐taking by individuals in relationships, organizations, and society. This paper presents two studies exploring what underpins defensive responses in the context of transgressions. In Study 1 ( N  = 202), participants recalled an interpersonal transgression, and in Study 2 ( N  = 143), omnivorous participants watched a guilt‐eliciting documentary about meat production practices. Both studies demonstrate that defensiveness increases in response to social/moral threat. Further, Study 2 demonstrates that this defensiveness can be reduced by addressing the underlying threat to social/moral identity via value affirmation, encouraging moral engagement, and repair.